Implementasi Sistem Good Corporate Governance Pada Perangkat Lunak Berbasis Website PT. Pusaka Bumi Transportasi - Pratama, Apriando; Wijaya, Alex (Technomedia Journal, 2023)
Good Corporate Governance is a company management system designed to improve the company's performance, taking into account the interests of other stakeholders, based on laws and regulations and generally accepted ethical values, as the main foundation in every business activity. -values ​​of integrity and applies the principles of Good Corporate Governance, namely transparency, accountability, independence, fairness, and responsibility. Therefore, a support application is needed to be able to facilitate and expedite the need for access to information regarding Good Corporate Governance by providing website-based Good Corporate Governance information system services. PT. Pusaka Bumi Transportation as one of the companies located in Muara Enim is seen as a relevant research place for students of the Faculty of Computer Science, Binadarma University. In this section the author will conduct research on software requirements at PT. Heirloom of the Earth Transportation. Here the author will implement a system of Good Corporate Governance at PT. Pusaka Bumi Transportation which will be built by the author himself. In this study, the author uses the Rational Unified Process application development method where there are 4 stages, namely Inception, Elaboration, Construction, and Transition. This research produces a software system of Good Corporate Governance which consists of 3 main aspects, namely recruitment, employee transfer, and flow documents that meet the 5 variables of Good Corporate Governance.